Moderate exercise improves depression parameters in treatment-resistant patients with major depressive disorder - Mota-Pereira, Jorge (2011)
Treatment-resistant major depressive disorder (MDD) is a complex condition, with very low remission rates. Physical exercise has been used, with some encouraging results, as an alternative therapy in other depressive disorders. This study assessed the impact on depression and functioning parameters of a moderate intensity exercise program, as an adjuvant to pharmacotherapy, in treatmentresistant MDD patients. Methods: 150 individuals with treatment-resistant MDD, defined as taking combined therapy in doses considered adequate for 9e15 months, without showing clinical remission, were initially screened. 33 were randomized to one of two groups: usual pharmacotherapy (N ¼ 11) and usual pharmacotherapy plus aerobic exercise (N ¼ 22). The exercise program consisted of home-based 30e45 min/day walks, 5 days/week, for 12 weeks, being 1 walk per week supervised. Results: The exercise group showed improvement of all depression and functioning parameters, as indicated by lower HAMD17, BDI and CGI-S and higher GAF (p < 0.05) at last observation compared both to baseline values and to control group. At the end of the study none of the participants in the control group showed response or remission, whilst in the exercise group 21% of participants showed response and 26% remission, although these differences were not statistically significant. Conclusion: A 12 week, home-based exercise program of 30e45 min/day walks, 5 days/week, improved depression and functioning parameters in treatment-resistant MDD patients, and contributed to remission of 26% of these patients. Moderate intensity exercise may be a helpful and effective adjuvant therapy for treatment-resistant MDD.